FAKTOR – FAKTOR YANG MEMPENGARUHI REALISASI DAN PENGEMBALIAN KREDIT USAHA RAKYAT - Anna Maria Lubis; Dwi Rachmina (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2011)
KUR (Kredit Usaha Rakyat) is a credit allocated for micro, small and medium enterprise which has economic feasibility but not yet bankable. Since April 2008, KUR realization in BRI unit X suffer from significant decrease cause by high credit arrears. This research analyze the factors affecting KUR realization and repayment. The results indicate that firms turnover, income level, business type, amount of credit and collateral value have significant effect on KUR realization. Meanwhile factors affecting the KUR repayment are sex, education, repayment period and installment and credit rate.